1996
DOI: 10.1021/jf950470q
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Structural Properties and Immunochemical Reactivity of Heat-Treated Ovalbumin

Abstract: Protein detection to certify foodstuff composition is frequently accomplished by immunochemical methods. Product processing (heating, pH change, etc.) usually alters protein structure and can modify immunochemical reactivity of the protein. We studied the structural changes caused by heating ovalbumin under different time and temperature conditions and the influence of heat on the immunochemical reactivity of ovalbumin. Differential scanning calorimetry (DSC), exposed sulfhydryl groups, and surface hydrophobic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 28 publications
3
25
0
Order By: Relevance
“…Heat-induced denaturation of ovalbumin results in exposure of these sulfhydryl groups (Beveridge & Arntfield, 1979;Rumbo et al, 1996). As shown in Fig.…”
Section: Sulfhydryl Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…Heat-induced denaturation of ovalbumin results in exposure of these sulfhydryl groups (Beveridge & Arntfield, 1979;Rumbo et al, 1996). As shown in Fig.…”
Section: Sulfhydryl Contentmentioning
confidence: 99%
“…Many studies have been conducted on the correlation between the structural properties of egg white proteins (mainly the abundant ovalbumin) and their functional properties. In these studies much attention was paid to the heat-induced changes in structural properties of proteins, leading to changes in the functional characteristics (Donovan, Mapes, Davis, & Garibaldi, 1975;Kato, Fujimoto, Matsudomi, & Kobayashi, 1986;Mine, Noutomi, & Haga, 1990;Mine, 1995;Rumbo, Chirdo, Fossati, & Anon, 1996). However, from these studies, little information can be deducted to describe these heat-induced changes in kinetic terms.…”
Section: Introductionmentioning
confidence: 99%
“…Breton, Phan Thanh, and Paraf (1988) found that affinity purified antibodies raised against native ovalbumin had higher avidity against heat-denatured ovalbumin than against the native ovalbumin molecule. Rumbo, Chirdo, Fossati, and Anon (1996) found that avidity peaked and then began to decrease as heating time increased. This trend held true for samples tested between 70 and 100°C.…”
Section: Indirect Elisa Of Dew and Wpc In Crabstickmentioning
confidence: 99%
“…For human consumption excessive heat-treatment of ovalbumin is relevant in view of the reported antigenic and allergenic properties of the native protein (Johnson and Elsayed, 1990;Kahlert et al, 1992), compared to heattreated forms (Ikura et al, 1992;Rumbo et al, 1996). Moreover, heat-treatment causes the protein to aggregate and allows the development of a gel structure (Weijers et al, 2004), a desired functionality for a food texturizer.…”
Section: Introductionmentioning
confidence: 99%